THE LISTENING COMPREHENSION DIFFICULTIES OF THE STUDENTS OF ENGLISH DEPARTMENT, MULAWARMAN UNIVERSITY - Ventje Jany Kalukar; Pradita Dinda Agtaviarini; Dian Anggriyani (Educational Studies: Conference Series, 2021)
The purposes of this study were to know the difficulties faced by the fourth semester students in Advanced Listening Comprehension Course at English Department, and to know strategies used by the fourth semester students in overcoming the difficulties in Advanced Listening Comprehension Course at English Department. The design of this study was descriptive with qualitative approach. The population was the fourth semester students at English Department in Mulawarman University that consisted of 63 active students of fourth semester students at English Department in Mulawarman University. Data was gathered by questionnaire and interview. The findings of this study showed that, the students had difficulties in listening comprehension and strategies to overcome it. It was based on three factors influencing their listening: listening materials, listener factors, and physical settings. In addition, the major problems encountered by students of English Department were: accents, pronunciation, speed of speech, insufficient vocabulary, different accent of the speakers, lack of concentration, and bad quality of recording. Furthermore, the strategies that the students implemented was using media as the learning tool. It can be concluded from this study that there were ten problems in students’ self learning that were found in analyzing students’ difficulties, they were : lack of vocabulary, poor grammar mastery, accent, pronunciation, lack of concentration, speed of speech, anxiety, noisy, inability to apply listening strategy, bad quality of recording.